1996
DOI: 10.1002/star.19960480509
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cyanoethyl Inulin, Aminopropyl Inulin and Carboxyethyl Inulin

Abstract: Inulin was cyanoethylated by reaction with acrylonitrile in the presence of aqueous sodium hydroxide. Products with a degree of substution (ds) from 0.2 to 1.6 were prepared. The materials were analyzed using NMR spectroscopy and GPC analysis. The nitrile groups of cyanoethyl inulin were converted into amino groups by reduction with sodium borohydride in the presence of a transition metal chloride (CoCl2.6H2O). Furthermore, the nitrile groups were hydrolyzed towards carboxylates using hydrogen peroxide in alka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 16 publications
1
32
0
Order By: Relevance
“…[16] O-(Aminopropyl)inulin (API) was selected as a starting material as it is easily accessible through the cyanoethylation of inulin. [17] Reduction of the nitrile groups was accomplished with Li metal in liquid ammonia/methanol at low temperature to yield the amino-substituted inulin API. [18] Studies have indicated that the cyanoethyl groups in cyanoethyl inulin (CEI) are distributed uniformly along the inulin chain and that within each fructose unit, the 4-position is the most reactive toward cyanoethylation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[16] O-(Aminopropyl)inulin (API) was selected as a starting material as it is easily accessible through the cyanoethylation of inulin. [17] Reduction of the nitrile groups was accomplished with Li metal in liquid ammonia/methanol at low temperature to yield the amino-substituted inulin API. [18] Studies have indicated that the cyanoethyl groups in cyanoethyl inulin (CEI) are distributed uniformly along the inulin chain and that within each fructose unit, the 4-position is the most reactive toward cyanoethylation.…”
Section: Resultsmentioning
confidence: 99%
“…[15] The coordination cage is completed by one bound water molecule. [15] For the API-DO3ASQ conjugates, the formation of Gd III complexes was achieved by using an NMR titration procedure in which complete complexation is detected by monitoring the 17 O NMR signal of the solvent water. [3] In a typical experiment, a solution of the ligand in D 2 O is placed in a 10 mm NMR tube and titrated with solid portions of GdCl 3´6 H 2 O at 75 8C while maintaining neutral pH.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature, various claims are made and attempts described to synthesize polysaccharides with primary or secondary amino functionalities (Cimecioglu, Ball, Kaoplan & Huang, 1994;Daly & Munir, 1984;Hebeish, Waly, Higazy & Abdel-Mahdy, 1994;Kerr & Neukom, 1952;Verraest, Silva, Peters & van Bekkum, 1996;Verraest, Zitha-Bovens & van Bekkum, 1998;Wolfrom, Taha & Horton, 1963). However, none of the routes to these are suitable for large scale synthesis.…”
Section: Introductionmentioning
confidence: 99%